2019
DOI: 10.1038/s41467-019-13263-6
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic polymer nanoparticles with controlled dimensions from the morphological transformation of isotropic seeds

Abstract: Understanding and controlling self-assembly processes at multiple length scales is vital if we are to design and create advanced materials. In particular, our ability to organise matter on the nanoscale has advanced considerably, but still lags far behind our skill in manipulating individual molecules. New tools allowing controlled nanoscale assembly are sorely needed, as well as the physical understanding of how they work. Here, we report such a method for the production of highly anisotropic nanoparticles wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 48 publications
(74 reference statements)
0
49
0
Order By: Relevance
“…[ 1 ] Recently, more attention has been paid to introducing motifs capable of forming directional, supramolecular interaction forces such as π–π interactions or hydrogen bonds (H‐bonds) that can allow to direct the polymer assembly into elongated structures, such as cylinders, that would otherwise not be accessible. [ 2–7 ] In particular, the so‐called supramolecular polymer bottlebrushes (SPBs) have gained increasing interest due to their potential applications in areas such as nanomedicine, [ 8 ] rheology [ 9 ] , electronics, and photonics. [ 10,11 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] Recently, more attention has been paid to introducing motifs capable of forming directional, supramolecular interaction forces such as π–π interactions or hydrogen bonds (H‐bonds) that can allow to direct the polymer assembly into elongated structures, such as cylinders, that would otherwise not be accessible. [ 2–7 ] In particular, the so‐called supramolecular polymer bottlebrushes (SPBs) have gained increasing interest due to their potential applications in areas such as nanomedicine, [ 8 ] rheology [ 9 ] , electronics, and photonics. [ 10,11 ]…”
Section: Methodsmentioning
confidence: 99%
“…Although there have been recent reports using more unusual interactions as the basis for seeded growth, such as hydrogen bonding, 198 π-π interactions 287 and metal-metal bonding 288 , we believe a priority for the field should be the identification of growth mechanisms that enable the controlled growth of nanostructures based on amorphous materials. A recently proposed approach, based on a morphological transformation process (MORPH) exploits supramolecular bonding to drive insertion of a polymer into a spherical seed nanoparticle, coupled with careful design of the polymers' physical properties, to control growth of amorphous, high aspect ratio wormlike nanoparticles 289 . A physical model developed to describe this 'morphological transformation' process suggested that it should be possible to use other supramolecular bonding interactions to achieve similar results.…”
Section: [H1] Outlookmentioning
confidence: 99%
“…Most peptide amphiphiles are especially proficient at forming rigid cylindrical micelles, because inter-amphiphile hydrogen bonding provides a strong driving force towards anisotropy. [42][43][44] In fact, considerable research has been dedicated to modulating this behavior in peptide-lipid conjugates, primarily by altering the peptide sequence to control inter-amphiphile interactions. [4,[45][46][47] This series of XTEN2-based PPAs have a self-assembly space that more closely resembles block copolymers, which typically have a narrow regime for anisotropic particles that are flexible.…”
Section: Ppas Can Access a Broad Range Of Self-assembled Morphologies By Adjusting Oligomer Tail Lengthmentioning
confidence: 99%